Implementing a Career Development Program for Student-Athletes - Sanders, Eric J. (My University, 1992)
When synthesized with a fundamental academic support program, a career development program can prove to be a valuable source of information and education. Guidance about careers and academic disciplines, plus the experiential opportunities that link classroom knowledge and practical experience, have been shown to be helpful in focusing the interests and energies of young adults. This article described the Wildcat Career Development Program, which was initiated at the University of Kentucky in the fall of 1991.
Keywords: career development